Evaluation of Platonia insignis Mart. (Bacuri Butter) and Biopolymers from the Puree of Allium cepa L. (Yellow Onion Bulb) for Wound Healing in Horses - Resende, André M.; Miranda, Beatriz A.; Silva, Luiza B.; Oliveira, Andressa B.; Castro, Márcio B.; Macêdo, Isabel L.; Dallago, Bruno S. L.; Barud, Hernane S.; Borges, Marco A. Costa; Ribeiro, Clovis A. [UNESP]; Dias, Diogenes S. [UNESP]; Campebell, Rita C. (MDPI, 2024)
Background/Objectives: Skin injuries are common in the equine clinical practice, requiring effective treatment to support natural healing. Bacuri butter is gaining attention for its potential in wound healing and its anti-inflammatory, antimicrobial, and antioxidant properties. Natural polymers such as onion (Allium cepa) bioplastics have been investigated for their potential as occlusive dressings and for tissue regeneration. Methods: This study evaluated the healing process of experimentally induced skin wounds on horses treated with bacuri butter, washed onion film, and unwashed onion film. Clinical and histopathological analyses of the wounds were conducted in six clinically healthy horses over 28 days, with a control group receiving Ringer’s lactate solution. The onion films were produced and characterized for their chemical structure and properties, while the bacuri butter was sourced and prepared for application. Results: All treatments, including the control group, promoted wound healing without relevant differences in wound contraction rates, gross aspect, or histopathological parameters. Conclusions: Therefore, despite minor variations observed in the clinical evaluations between the treatment groups, the bacuri butter or onion biopolymer showed no significant healing effect on skin wounds in horses. Additionally, this study showed the potential of equine models in testing novel therapeutic approaches for wound healing, benefiting both veterinary and human medicine.
Keywords: bacuri butter; horses; onion biopolymer; wounds healing